Evaluating distributions for the timing of respiratory disease in feedlot cattle and determining risk factors associated with mid- and late-feeding stage bovine respiratory disease - Smith, Kristen Joy Sinclair (Kansas State University, 2022)
Understanding the epidemiology of bovine respiratory disease (BRD) in feedyard cattle is an important part of improving the efficiency, economics, and animal husbandry of the cattle industry. Recent concern has developed over a suspected increase in BRD occurring later in the feeding period than previously noticed. Three studies were conducted using retrospective industry data to evaluate any relevant risk factors associated with the timing of BRD morbidity and mortality. The first study identified temporal distributions of first treatment for BRD morbidity, days from feedlot arrival to first pull for an animal that subsequently died, and days on feed (DOF) from first pull for BRD until death attributed to BRD. These were visually compared for steers and heifers that arrived in the 700 to 800 lb weight category across the quarters of the year. In general, heifers had a later DOF for all three outcomes compared to steers, and the quarter of arrival that most often was later for all three categories was Q2 (April-June). The second study utilized cluster analysis to group cohorts into the most similar disease pattern based on number of BRD pulls by DOF. Clusters were analyzed as early-, mid-, or late-feeding stage cohorts and evaluated for risk factors associated with the timing of disease. The only factor significantly (P<0.05) associated with cohort-level BRD morbidity timing was quarter of arrival. Cattle that arrived in Q2 were more probable to be mid- or late-feeding phase (5.5%, 10.2% respectively) morbidity at the cohort level. The third study evaluated the timing of BRD morbidity and mortality for individual animal records. Cattle demographic factors were used to evaluate associations with the probability of an individual animal first treatment BRD or mortality being early-, mid-, or late-feeding stage. In general, heifers, heavier animals at arrival, and cattle that arrived at the yard in the first and second quarter were the most likely demographic categories to have an initial diagnosis of BRD in the mid- or late-stage of the feeding phase. Further understanding of typical patterns of disease could lead to the ability to modify prevention or intervention techniques to improve cattle health.
Keywords: Bovine respiratory disease; Disease timing; Late-feeding-stage